Wind speed data analysis for predictions of sea waves in Bitung Coastal Waters - Koagouw, Joanes E; Mamuaya, Gybert E; Tarumingkeng, Adrie A; Angmalisang, P A (AQUATIC SCIENCE & MANAGEMENT, 2013)
Coastal area of Bitung Municipality is one of the economical activities centers in North Sulawesi Province such as for land-uses and the exploitation of natural resources. Those activities are exaggerating day bay day and tended to be uncontrollable. The excess of those conditions, it has been recorded the change of waves in Bitung waters that has impacts to coastal areas and can affect the utilization of coastal and marine resources. This research was aimed to observe waves altitude variations in Bitung waters with Svedrup Munk and Bretchsneider (SMB) method that had been used to predict waves altitudes. The results showed that the wind speed during West Season was 0.33 m and were dominant to the East, while during East season was 0.91m from South-East to North-West, and then on transition period (March to May) was 1.08m from South-East to East. The results of those wind speed to the waves altitudes in Bitung waters is discussed in this paper© Pesisir pantai Kota Bitung merupakan salah satu pusat aktivitas ekonomi (misalnya pemanfaatan lahan dan eksploitasi sumberdaya) di Provinsi Sulawesi Utara. Aktivitas tersebut semakin hari semakin meningkat dan memiliki kecenderungan tidak terkontrol. Akibat dari keadaan tersebut, telah terjadi perubahan fenomena gelombang di perairan Bitung yang berdampak pada keberadaan daerah pesisir pantai di mana hal ini dapat mengganggu aktivitas pemanfaatan sumberdaya pesisir dan laut tersebut. Penelitian ini bertujuan untuk mengetahui variasi tinggi gelombang di perairan Bitung dengan menggunakan metode Svedrup Munk and Bretchsneider (SMB) yang biasa digunakan untuk peramalan tinggi gelombang signifikan. Hasil penelitian menunjukkan bahwa kecepatan angin pada Musim Barat sebesar 0,33 meter dan dominan ke arah Timur, sementara pada Musim Timur sebesar 0,91 meter dari arah Tenggara ke Barat Laut, serta pada Musim Peralihan (antara bulan Maret-Mei) adalah sebesar 1,08 meter dari arah Tenggara dan Timur. Pengaruh kecepatan angin tersebut terhadap gelombang laut di perairan Bitung dibahas dalam tulisan ini©